Chaperone systems of the endoplasmic reticulum - Hendershot, Linda M. (Henry Stewart Talks, 2012)
Communication between cells, Angiogenesis, Secretion of effector molecules, Cell migration/homing, Proteins synthesis & folding, Molecular chaperone families in the ER, Antibody formation, BiP: a soluble Hsp70 protein, ATPase and DnaK peptide binding domains, CH1 domain, The formation of disulfide bonds, ATPase cycle of BiP, Disruption of BiP/GRP78 gene in mice, Highly virulent subtilase toxin, BiP functions in ER, ER DnaJ proteins, Gal-4-BiP ATPase domain fusion protein, BAP/Sil1: a nucleotide releasing factor, Potential consequences of BAP/Sil1 loss and mutations, The family of large Hsp70 proteins, The two functions of GRP170, GRP94 as an essential gene- Immunophilins, lymphoid specific chaperone: pERp1